Cost Leadership or Diversification? Assessing the Business Strategies of PV Manufacturers Using Case Studies from the USA and the UK - Gazis,E; Candelise,C; Winskel,M (2013)
The recent explosive growth of the PV sector combined with the multiple technological advancements have allowed for extensive experimentation in terms of applications and business models. This paper follows on a previous market assessment and offers a mapping of the various business strategies adopted by PV firms. It investigates real case-studies to analyse the benefits and dangers related to diversification through product and market differentiation. Finally it provides insights for the growth potential of such firms taking into consideration not only the techno-economic characteristics that are intrinsic to each one, but also the wider socioeconomic environment. The analysis combines literature research with original empirical evidence gathered using interviews with PV experts and comparative firm-level case studies. It then draws upon innovation studies, technological transitions and business literature to provide a novel analytical framework for the understanding of the factors facilitating or hindering the successful commercialisation of innovative PV applications. This work is part of the EPSRC’s Supergen PV21 Consortium (PV Materials for the 21st Century) and as such it draws upon leading expertise in TF PV technologies.